Two-Dimensional Electronics - Prospects and Challenges (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
During the past 10 years, two-dimensional materials have found incredible attention in the scientific community. The first two-dimensional material studied in detail was graphene, and many groups explored its potential for electronic applications. Meanwhile, researchers have extended their work to two-dimensional materials beyond graphene. At present, several hundred of these materials are known and part of them is considered to be useful for electronic applications. Rapid progress has been made in research concerning two-dimensional electronics, and a variety of transistors of different two-dimensional materials, including graphene, transition metal dichalcogenides, e.g., MoS2 and WS2, and phosphorene, have been reported. Other areas where two-dimensional materials are considered promising are sensors, transparent electrodes, or displays, to name just a few. This Special Issue of Electronics is devoted to all aspects of two-dimensional materials for electronic applications, including material preparation and analysis, device fabrication and characterization, device physics, modeling and simulation, and circuits. The devices of interest include, but are not limited to transistors (both field-effect transistors and alternative transistor concepts), sensors, optoelectronics devices, MEMS and NEMS, and displays.